If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying m + 2.7 = -4.5 Reorder the terms: 2.7 + m = -4.5 Solving 2.7 + m = -4.5 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-2.7' to each side of the equation. 2.7 + -2.7 + m = -4.5 + -2.7 Combine like terms: 2.7 + -2.7 = 0.0 0.0 + m = -4.5 + -2.7 m = -4.5 + -2.7 Combine like terms: -4.5 + -2.7 = -7.2 m = -7.2 Simplifying m = -7.2
| 9-3x=7x-11 | | 52=(3x) | | -22p=-231 | | x^2+4x-40=5 | | 6w-6= | | x^8=36x^6 | | x^2-4x-40=5 | | n+n+2=51 | | -6x+9is=to-21 | | 124=76+32x | | 18x+7=2x | | 334=-7(1-7x)-2 | | x^2+5-30=0 | | v/12=1 | | 52=(3x)+(42x) | | Y+x=325 | | n=687/24(-15) | | x^7=64x^5 | | Y-x=325 | | 3x-8=7-2x | | c/5.3+8.3=11.3 | | m+8=2 | | 2x^2+5=x^2-5x-1 | | 7d=-28 | | 23y=-92 | | -12x+35=0 | | Y=325-x | | 5+2x=65 | | 23y=-28 | | 7x+9-3x=-11 | | x+-5=4 | | 50=1.5x^2 |